Graphical user interface development of risk assessment identification for appropriate lightning protection system / Nur Hardhila Othman - Othman, Nur Hardhila (2006)
There are two types of lightning strikes that need to be protected which are direct strikes and indirect strikes (transient overvoltage). Field studies of both types of lightning strike show that the lightning protections system (LPS) can be provided by determining the value of risk assessment or risk factor. This thesis describes the progress of interactive graphical user interface (GUI) for calculating the value of risk assessment or risk factor. The GUI determines the value of risk assessment or risk factor and suggests the suitable lightning protection. The developed application will help end-users in determining the value of risk assessment or risk factor in an efficient manner. It is also shows the capability of MATLAB GUI programming in technical application.